The application of the multivariate comparative analysis to a company's financial performance evaluation and benchmark forecasting - Szandula, Jacek; Szpulak, Aleksandra (Zastosowanie wielowymiarowej analizy porównawczej do oceny i prognozy kondycji finansowej przedsiębiorstwa na tle branży, 2011)
A company’s financial performance is a complex phenomenon. At least several different financial ratios are required to describe it thoroughly. In this paper problems associated with a company’s financial performance evaluation and forecasting have been discussed in comparison to other companies in the same industry. The multivariate comparative analysis and the Monte Carlo simulation methods have been employed in this study. As far as creating a company ranking is concerned, a procedure based on the distribution function of the synthetic financial performance ratio has been applied.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 196, s. 92-110
Keywords: analiza porównawcza; wielowymiarowa analiza porównawcza; prognozowanie; finanse przedsiębiorstwa; comparative analysis; multi-dimensional comparative analysis; forecasting; enterprise finance